Pragmatic Expression of Bedhaya Sukma Raras: a Reactualization of Holisticity in Life - Maryono Maryono; Midiyanto Midiyanto (Gelar : Jurnal Seni Budaya, 2022)
The Bedhaya Sukma Raras dance by Hadawiyah Endah Utami,  presented at a gathering of choreographers, was inspired by the journey of human life as it moves towards death. The complementary forms of verbal and nonverbal components in Bedhaya Sukma Raras implicitly offer a concept encased in the aesthetic expression of the dance about human awareness of doing good throughout the transient life in this world, in order to welcome an afterlife that is immortal and full of joy. This research uses a qualitative methodology. The data collection strategies include a library study, interviews, a visual study of dance recordings, an audio study of music recordings, documentation and study of archives of verbal transcripts of literature about songs and vocabulary of dance movements. The results show that in principle human life must seek to preserve a balance between the world and the hereafter. This means that microcosmically, in fulfilling their daily needs, human beings must work hard, prioritize virtue, and pray for God’s guidance so that macrocosmically, in the afterlife their sins will be forgiven and they will enter the heaven of the Creator.